Aerobic exercise and cannabidiol supplementation modulate prostate Akt gene expression in high-fat diet-fed rats: Mechanistic insights into obesity-driven prostate cancer risk - Marzieh Hafezi Eirdmousa; Mandana Gholami; Heshmatollah Parsian; Hossein Abed-Natanzi (Journal of Exercise & Organ Cross Talk)
Epidemiological evidence indicates that obesity is associated with accelerated prostate cancer progression and elevated mortality rates. However, the underlying physiological mechanisms linking obesity to prostate cancer pathogenesis remain unclear. This study aimed to examine the effects of six weeks of moderate-intensity aerobic training combined with cannabidiol (CBD) supplementation on prostate protein kinase B (Akt) gene expression in high-fat diet (HFD)-induced obese male rats. Forty male Wistar rats (240 ± 20 g) were randomly assigned to five experimental groups: healthy control, HFD, HFD+exercise, HFD+CBD, HFD+exercise and CBD (n=8 per group). CBD was administered via oral gavage at 100 mg/kg, five days per week for six weeks. The aerobic exercise protocol consisted of treadmill running at progressive intensities, ranging from 15 m/min for 30 min to 27 m/min for 60 min, five days per week for six weeks. Following the intervention, prostate tissue was extracted for quantitative analysis of Akt gene expression. Statistical analysis revealed that aerobic exercise significantly modulated Akt gene expression (P=0.015). Similarly, CBD administration exerted a significant effect on Akt expression (P=0.004). However, no significant interactive effect was observed between aerobic exercise and CBD (P=0.068). These findings suggest that both aerobic exercise and CBD independently influence Akt signaling pathways, potentially through anti-inflammatory mechanisms, which may contribute to prostate cancer prevention. Further research is warranted to elucidate the precise molecular interactions involved.